We have to find x given that : tan^2 x - 4sec x + 5 = 0

(tan x)^2 - 4sec x + 5 = 0

=> ( 1 - (cos x)^2)/( cos x)^2) - 4/ cos x + 5 = 0

let cos x = y

=> (1 -...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to find x given that : tan^2 x - 4sec x + 5 = 0

(tan x)^2 - 4sec x + 5 = 0

=> ( 1 - (cos x)^2)/( cos x)^2) - 4/ cos x + 5 = 0

let cos x = y

=> (1 - y^2)/y^2 - 4/y + 5 = 0

=> (1 - y^2) - 4y + 5y^2 = 0

=> 4y^2 - 4y - 1 = 0

=> (2y - 1)^2 = 0

=> 2y = 1

=> y = 1/2

=> cos x = 1/2

=> x = arc cos (1/2)

x = pi/3 + 2*pi

**The angle x = pi/3 + 2*pi**